Flow behavior and processing map of newly developed ECO-AlMag8 alloy during hot compression - Majid Seyed Salehi; Ali Sonboli; Nam Seok Kim; Bong Hwan Kim; Shae Kwang Kim; Ghasem Eisaabadi B․ (Results in Engineering)
The flow behavior and processing map of ECO-AlMg8 alloy are investigated by hot compression of cylindrical samples machined from homogenized direct-chill cast billets at temperatures ranging from 300–450 °C and strain rates of 0.001 to 1 s⁻¹ using a Gleeble-3500 thermo-mechanical simulator. Subsequently, the hot deformation behavior of the alloy was modeled using the Sellars-Arrhenius constitutive equation. The calculated hot deformation activation energy of the ECO-AlMag8 (157.1 kJ.mol⁻¹) was considerably higher than that of self-diffusion of pure Al (122 kJ.mol⁻¹), which suggests that the flow behavior, dynamic recovery, and dynamic recrystallization of the alloy are controlled by the diffusion of impurity atoms such as Fe and Mn. Furthermore, the processing map of the alloy indicated that the safe hot deformation regime occurred at high temperatures (350–450 °C) and low strain rates (0.001–0.01 s⁻¹). This finding was further supported by optical microscopy and EBSD analysis, which revealed dynamic recovery and recrystallization within the safe deformation zone. In contrast, both the processing map and microstructural analysis confirmed that low temperatures and high strain rates resulted in hot deformation instability due to the formation of shear bands.